2022
DOI: 10.3390/nano12234252
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Silver Nanoparticles for Inkjet-Printable Conductive Inks

Abstract: The large-scale manufacturing of flexible electronics is nowadays based on inkjet printing technology using specially formulated conductive inks, but achieving adequate wetting of different surfaces remains a challenge. In this work, the development of a silver nanoparticle-based functional ink for printing on flexible paper and plastic substrates is demonstrated. Amphiphilic silver nanoparticles with narrow particle size distribution and good dispersibility were prepared via a two-step wet chemical synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Binding Energy in Sample, eV 1% Ag@BVO 8% Ag@BVO 15% Ag@BVO 5% Fe@BVO 27.5% Fe@BVO 50% In general, smaller Ag nanoparticles (AgNPs) are more reactive than their larger counterparts and have a partial electron-donating character [46,47]. With lower Ag In general, smaller Ag nanoparticles (AgNPs) are more reactive than their larger counterparts and have a partial electron-donating character [46,47]. With lower Ag loading, it is likely that smaller nanoparticles are obtained, which are more susceptible to oxidation.…”
Section: Spectramentioning
confidence: 99%
“…Binding Energy in Sample, eV 1% Ag@BVO 8% Ag@BVO 15% Ag@BVO 5% Fe@BVO 27.5% Fe@BVO 50% In general, smaller Ag nanoparticles (AgNPs) are more reactive than their larger counterparts and have a partial electron-donating character [46,47]. With lower Ag In general, smaller Ag nanoparticles (AgNPs) are more reactive than their larger counterparts and have a partial electron-donating character [46,47]. With lower Ag loading, it is likely that smaller nanoparticles are obtained, which are more susceptible to oxidation.…”
Section: Spectramentioning
confidence: 99%
“…Nanosilver has been explored for its potential in electronic applications, such as conductive inks, transparent conductive films, and sensors. Studies have reported the use of nanosilver for producing highly conductive and flexible electronic devices [48,14,78,39] .…”
Section: Electronicsmentioning
confidence: 99%
“…IPL is a non-laser, high-intensity white light emitted from a xenon flash lamp. With processing times on the order of microseconds to milliseconds, it is highly compatible with inkjet printing and other highthroughput printed electronics fabrication technologies [40][41][42].…”
Section: Introductionmentioning
confidence: 99%